2014
DOI: 10.1186/s13058-014-0454-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Nuclear factor of activated T cells 5 maintained by Hotair suppression of miR-568 upregulates S100 calcium binding protein A4 to promote breast cancer metastasis

Abstract: IntroductionThe onset of distal metastasis, which underlies the high mortality of breast cancers, warrants substantial studies to depict its molecular basis. Nuclear factor of activated T cells 5 (NFAT5) is upregulated in various malignancies and is critically involved in migration and invasion of neoplastic cells. Nevertheless, the metastasis-related events potentiated by this transcriptional factor and the mechanism responsible for NFAT5 elevation in carcinoma cells remain to be fully elucidated.MethodsThe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 37 publications
1
38
1
Order By: Relevance
“…Treatment of calycosin or genistein also decreased phosphorylation of Akt, and also the expression of its downstream target, HOTAIR [126]. Mechanistic studies show that HOTAIR suppress a miRNA (miR-568) and in turn augments the NFAT5 (Nuclear factor of activated T cells 5) expression in metastatic breast cancers [127]. Another study showed that downregulation of miR-7 in breast cancer stem cells may be indirectly attributed to HOTAIR by modulating the expression of HOXD10 that promotes the expression of miR-7.…”
Section: Hotair and Cancermentioning
confidence: 99%
“…Treatment of calycosin or genistein also decreased phosphorylation of Akt, and also the expression of its downstream target, HOTAIR [126]. Mechanistic studies show that HOTAIR suppress a miRNA (miR-568) and in turn augments the NFAT5 (Nuclear factor of activated T cells 5) expression in metastatic breast cancers [127]. Another study showed that downregulation of miR-7 in breast cancer stem cells may be indirectly attributed to HOTAIR by modulating the expression of HOXD10 that promotes the expression of miR-7.…”
Section: Hotair and Cancermentioning
confidence: 99%
“…Li JT. et al, identified that HOTAIR could suppress the miR-568 to up-regulate the expression of S100 calcium binding protein A1 (S100A), and then facilitates the metastasis of breast cancer 45. The B-Raf proto-oncogene, serine/threonine kinase (BRAF) pseudogene 1 is a newly reported lncRNA that functions as a ceRNA for BRAF, in part by sponging miR-30a, miR-182, and miR-87646.…”
Section: Working Mechanisms Of Lncrnasmentioning
confidence: 99%
“…Dextran nanoparticles can deliver chemotherapy to the nucleus, which may be used to attach cytotoxic agents to lncRNAs 66. The plasmid DTA-H19 was designed to express a diphtheria toxin subunit controlled by the H19 promoter 72, 73, which could be injected into tumor and lead to a H19-dependent activation of diphtheria toxin within the tumor 45. Another emerging method is to increase the activity of tumor suppressor by neutralizing the inhibitory effects of lncRNAs through antisense oligo nucleotides 66.…”
Section: Medical Applications Of Lncrnas In Human Diseasesmentioning
confidence: 99%
“…113,117 S100A4 is upregulated by canonical Wnt signaling, and inhibition of b-catenin decreases tumor cell migration and invasion through downregulation of S100A4. 106,109 NFAT is expressed in metastatic breast cancer and also transcriptionally activates S100A4, 118 Interestingly, NFAT activation is driven by calcium influxes during epithelial scattering of MDCK cells, 31 indicating that there might be multiple connections between S100A4 and increased intracellular calcium concentration in EMT.…”
Section: Molecular Basis Of Calcium-mediated Changes In Actin Dynamicmentioning
confidence: 99%